Binding of Novobiocin Paves the Way for Inhibition of DEAH-box Helicase 8 - Ajmal, Mohammad Rehan; Almutairi, Fahad Mohammad; Hussain, Arif; Ullah, Mohammad Fahad; Ahmad, M Ayaz; Abdelhameed, Ali Saber; Arif, Hussain (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: DEAH-box helicase 8 (DHX8) is a crucial DEAH-box RNA helicase involved in splicing and required for the release of mature mRNA from the splice. Here, we report the interaction study of human DHX8 and four test compounds namely etoposide, netropsin, nogalamycin, and novobiocin. Materials and Methods: Molecular docking and fluorescence emission spectra techniques were employed to determine the binding and inhibitory effect of test compounds. Results: Our docking and fluorescence emission spectra results showed that DHX8 has a good binding preference for novobiocin among these four test compounds. Moreover, fluorescence emission spectra of DHX8 with novobiocin also revealed the 2.5 µM concentration is an effective novobiocin concentration to inhibit the activity of DHX8. Conclusion: These findings provide an in-depth understanding of the inhibition of DHX8 and contribute insights towards the development of novobiocin as a therapeutic molecule against the DHX8 in targeted diseases.
Keywords: DEAH-box helicase; DHX8; Novobiocin; Splicing; Therapeutics